Social capital and chemsex initiation in young gay, bisexual, and other men who have sex with men: the pink carpet Y cohort study - Rayner Kay Jin Tan; Caitlin Alsandria O'Hara; Wee Ling Koh; Daniel Le; Avin Tan; Adrian Tyler; Calvin Tan; Chronos Kwok; Sumita Banerjee; Mee Lian Wong (BMC, 2021)
Abstract Background Young gay, bisexual, and other men who have sex with men (YMSM) are especially vulnerable to the risks associated with sexualized substance use, or 'chemsex'. Engaging in chemsex established as a major risk factor for Human Immunodeficiency Virus (HIV) acquisition, and is thus a public health issue of increasing urgency. This paper attempts to explore the association between measures of social capital and patterns of sexualized substance use among a sample of YMSM in Singapore. Methods Results of this study were derived from baseline data of the Pink Carpet Y Cohort Study in Singapore, comprising a sample of 570 HIV-negative YMSM aged 18 to 25 years old. Latent class analysis was employed to identify classes with similar patterns of sexualized substance use, and multinomial logistic regression was employed to examine associations between class membership and proxy measures of social capital, including age of sexual debut, bonding and bridging social capital, connectedness to the lesbian, gay, bisexual and transgender community, and outness. Results Latent class analysis revealed three classes of YMSM based on their histories of sexualized substance use, which we labelled as 'alcohol', 'poppers', and 'chemsex'. Multivariable analyses revealed that participants who were older (aOR = 1.19, p = 0.002) and who identified as gay (aOR = 2.43, p = 0.002) were more likely to be in the poppers class compared to the alcohol class. Participants with a later age of sexual debut were increasingly less likely to be in the poppers (aOR = 0.93, p = 0.039) and chemsex classes (aOR = 0.85, p = 0.018), compared to the alcohol class. Conclusions Varying measures of social capital such as an earlier age of exposure to sexual networks may predispose YMSM to greater opportunities for sexualized substance use. Future interventions should target YMSM who become sexually active at an earlier age to reduce the risks associated with sexualized substance use.